Conformational equilibria in the activation of cystine-knot hormone receptors - Zhen Gong; Wayne A. Hendrickson (Proceedings of the National Academy of Sciences, 2026)
Human glycoprotein hormones such as thyroid-stimulating hormone (TSH) and follicle-stimulating hormone (FSH) belong to a broader family of cystine-knot hormones (CKHs), all of which act through leucine-rich-repeat (LRR)-containing G protein–coupled receptors (LGRs) with which they have coevolved from evolutionary predecessors in metazoan animals. There is substantial evidence for LGR dimers being required in the transmission of G-protein signals elicited by mammalian CKHs acting on their cognate LGRs. Yet, human LGRs are monomeric as extracted from cell membranes and also in cryo-EM structures, both when in apo, inactive state and when hormone bound in an LRR-elevated active state. Fortunately, the LGR from the nematode Caenorhabditis elegans ( Ce LGR) remains dimeric as detergent extracted for structure determination. In this study, we synthesize structural information from Ce LGR, Hs TSHR, and the other human LGRs together with biophysical evidence about physiological dimers to produce a theoretical description of conformational equilibria involved in CKH activation of LGRs. We develop a theory for the equilibria among conformations that govern signal transmission from hormone to G protein, we define the transitions of receptor activation in quantifiable terms, and we build and validate energetically feasible models for Ce LGR and Hs TSHR in their relevant 0:2, 1:2, and 2:2 hormone:receptor complexes. These developments provide a framework for understanding of signaling through CKH receptors and for devising structure-based hypotheses to test such conceptions.